0922 A Preliminary Study Of Sleep Apnea Hypopnea Syndrome Of HIV Infected Persons In HIV Clinics. (27th April 2018) - Lin, W; Chen, Y; Chen, C; Liu, H; Lin, C; Ko, N
Abstract: Introduction: Sleep apnea-hypopnea syndrome (SAHS) is a treatable and manageable disease. This study aimed to identify the percentage of SAHS among HIV-infected persons and to determine the independent predictors of those having SAHS. Methods: A cross-sectional study was conducted at an AIDS designed hospital in southern Taiwan. Inclusive criteria were HIV-infected persons (a) at least 20 years old, (b) free of psychiatric history, (c) not being treated with SAHS. Eligible participants were assessed initially with the Chinese version of Pittsburgh Sleep Quality Index (CPSQI). If participants shown CPSQI greater than 5 or self-reported sleep problems were referred to further examination using unattended polysomnography (PSG). Demographic questionnaire and snore outcomes survey (SOS) scale were also performed. SAHS was defined by apnea and hypopnea index (AHI) over than 5. The associated between independent predictors and SAHS was analyzed using linear regression analysis after adjusting p-value from binary analysis lower than 0.1. Results: A total of 33 HIV-infected men (mean age 34.6 years, mean BMI 23.6 kg/m 2 ) completed the whole study. The percentage of SAHS among HIV-infected persons was 54.5%. One-fifth (21.2%) of HIV-infected persons were diagnosed as moderate-severe SAHS (AHI≥15). Increasing AHI level was significantly associated with age (B=0.69, P=0.02), BMI (B=2.73, P=0.01) and SOS scores (B=-0.39, P=0.01). Conclusion: Our study results suggested to routinely assess sleep problems for HIV-infected persons to early detection and early treatment of SAHS, especially in older age, obesity and snorer. Support (If Any): N/A.